Public law after the Human Rights Act - Hickman, Tom (Tom R.) (Hart Pub., 2010)
What is the Human Rights Act? What is its relationship to the common law? Is there a need to invent new doctrines of public law to accommodate the Act? Will it lead to the extinction of established doctrines? What should be the effect of the Act on the structure of public law as a whole?